Digital Watermarking using Lifting Wavelet Transform of Crowd Sourced Images - Kumar Shrivastava, Shailesh; S.K. Mahendran, Dr (International Journal of Engineering and Technology, 2018)
Capturing of digital images through Mobile based e-governance applications are growing day-by-day and issue related to protection of copyrights of digital images has become very critical. Protecting these high-volume geo-tagged time stamped digital images captured through android apps and ensuring that these images are suitable for social audit are key challenge for todayâ€™s application development. Digital image watermarking is a process by which secret information can beÂ in digital images so that it is possible to guard copyrights. The paper discusses an efficient digital image watermarking system using lifting wavelet transform. The proposed algorithm aims to minimize distortion of selected watermarked image. The performance of the algorithm has been tested using available images with MATLAB and their results have been properly analyzed with existing methods. The variance value between coefficients of lifting wavelet transform (LFT) in a block with size 2 x 2 has been chosen for embedding the binary watermark and the blocks are also then shuffled randomly. The result of various experiments has demonstrated that the developed algorithm is robust against various types of attacks being applied.Â Â